The analgesic effect of different interactive modes of virtual reality: A prospective functional near-infrared spectroscopy (fNIRS) study - Deng, Xue; Jian, Chuyao; Yang, Qinglu; Jiang, Naifu; Huang, Zhaoyin; Zhao, Shaofeng (Frontiers in Neuroscience, 2022)
Virtual reality (VR) has been shown its effectiveness for pain relief. However, its optimal interactive mode is yet unclear, with rare objective measurements to explore its neural mechanism. Objective: This study primarily aimed at investigating the analgesic effect of different VR interactive modes via functional near-infrared spectroscopy (fNIRS) and exploring its correlations with subjectively reported VR experience through self-rating questionnaire. Methods: 15 healthy volunteers (Age: 21.93±.59 years, 11 female, 4 male) were enrolled in this prospective study. Three rounds of interactive modes, including active mode, motor imagery (MI) mode, and passive mode were successively facilitated under consistent noxious electrical stimuli (Electrical intensity: 23.67±5.69mA). Repeated measures of analysis of variance (ANOVA）was utilized to examine its pain relief status and cortical activation, with post-hoc analysis after Bonferroni correction performed. Spearman’s correlation test was utilized to explore the relationship between VR questionnaire (VRQ) items and cortical activation. Results: A larger analgesic effect in the active (-1.4(95%CI, -2.23 to -.57), p=.001) and MI modes (-.667(95%CI, -1.165 to -.168), p=.012) was observed compared to the passive mode in the self-rating pain score, with no significant difference reported between the two modes (-.733(95%CI, -1.631 to .165), p=.131), associated with diverse activated cortical region of interest (ROI) in charge of motor and cognitive function, including left motor-cortex (LM1), dorsal-lateral prefrontal cortex (LDLPFC), somatosensory cortex (LS1), visual cortex at occipital lobe (LOL) and pre-motor cortex(LPMC). On the other hand, significant correlations were found within VRQ items, including pain, attention, immersion and pain distraction (r= -.25 to .729 , p<0.05) as well as its correlation with different cortical ROIs (r= -.629 to .772, p<0.05) and the corresponding channels (r=-.599 to .788, p<0.05). Conclusion: Our findings suggest that VR can be considered as an effective non-invasive approach for pain relief via modulating cortical pain processing. A better analgesic effect can be obtained by exciting and integrating cortical ROIs in charge of motor and cognitive functions. The interactive mode can be feasibly tailored in line with client’s characteristics in spite of diverse cortical activation status when equivalent analgesic effect can be obtained.